Eksistensi Penggunaan Rupiah dalam Transaksi Elektronik untuk Mewujudkan Kesejahteraan Rakyat - Ellizabeth; Dewi Iryani; Hartana (Jurnal Hukum Lex Generalis, 2025)
The development of digital payment technology has changed the landscape of the payment system in Indonesia, with electronic money (e-money) becoming increasingly popular as an alternative to cashless payments. This study aims to analyze the legal protection of the use of the rupiah currency amidst the widespread use of electronic money in Indonesia. The research method used is a normative legal research method with a qualitative approach, utilizing secondary data through literature studies and documentation. The results of the study indicate that there are legal problems in the implementation of e-money related to Law Number 7 of 2011 concerning Currency which requires the use of the rupiah in all transactions in Indonesia. Problems arise when some merchants refuse cash payments and only accept e-money, which contradicts the legal provisions prohibiting the refusal of payments using the rupiah with a maximum criminal penalty of one year imprisonment and a fine of up to IDR 200 million. Bank Indonesia Regulation Number 20/6/PBI/2018 concerning Electronic Money has not explicitly regulated the position of cash in the era of payment dualism, thus creating legal uncertainty. This study recommends the need for regulatory harmonization that accommodates non-cash payment policies without eliminating the public's right to use cash, as well as the importance of educating the public about the rights, risks, and responsibilities of using electronic money.